(untitled) (Journal of Fiber Bioengineering and Informatics, 2015)
Diameter of spacer filament, thickness of spacer fabric, and warp threads per centimeter and weft threads per centimeter on plate compression of woven spacer fabric was studied by finite element method. Compression force and strain curves were acquired by ABAQUS software and compression indices were featured, including compression work, maximum compression force and compression index. Small relative errors of compression indices between experimental and theoretical results demonstrated that it was feasible to use finite element method to predict plate compression performance of spacer fabric. Woven spacer fabrics with different structure were designed and theoretical results showed that the thicker the spacer filament, the greater the three compression indices. Moreover, compression stress distribution of spacer fabrics indicated that stress of spacer filament was much larger than that of warp threads and weft threads of surface fabrics.